Analysis of the Determinants of Innovation in Developing Countries: A Vector Auto-regression Approach - Asunka, Benjamin Azembila; Ma, Zhiqiang; Li, Mingxing; Aganda, Oswin Anaba (International Journal of Scientific Research and Management (IJSRM), 2020)
Several factors account for innovation output in developed economies as documented in extant literature. The objective of this study is to make a case for a multi-faceted approach to innovation in developing countries. To analyze various factors affecting innovation, a sample of 43 developing countries is taken and the period of study is between 2009 and 2018.  A vector auto-regression model is used in a panel data setting to test the effect of various variables on innovation at country level, a granger causality test is also conducted to determine the causal relationship among these factors that together can spur innovation activities. Findings suggest a strong influence of R&D and government procurement of technology on the advancement of innovation. R&D is largely affected by the quality of research institutions and university-industry collaborative research, thus showing the strength of the effect of these variables on innovation. Scientists and engineers with requisite expertise greatly improve a country’s innovation efforts, however, developing countries do not benefit fully from the economic value of these experts. These results show that an integration of all these factors is a good approach to enhancing innovation in developing economies.